ANALYSIS OF THE EFFECT OF INFORMATION TECHNOLOGY USE, DIGITAL FINANCIAL LITERACY, AND INTERNAL CONTROL SYSTEM ON EMPLOYEE PERFORMANCE AT THE DPRD SECRETARIAT OF SLEMAN DISTRICT DPRD - Rafika Salamah, Isna; Sumaryanto, Sumaryanto (JURNAL EKBIS, 2024)
This study aims to determine the effect of the use of information technology, digital financial literacy, and internal control systems on employee performance at the Sleman Regency DPRD Secretariat office. This type of research is quantitative. The sampling technique used was purposive sampling, using a sample of 121 employees and the data was obtained through a questionnaire. The data that has been obtained is then processed using SPSS 20. The results of this study indicate that information technology, digital financial literacy, and internal control systemshas an influence on employee performance with a total of 53.2% and the remaining 46.8% is caused by other factors that were not studied.